2018
DOI: 10.1186/s12933-018-0712-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of complications at diagnosis of T2DM and during follow-up by BMI and ethnicity: a matched case–control analysis

Abstract: AimsTo estimate the risk of developing long-term major cardiovascular and renal complications in relation to levels of body mass index (BMI) in a population of White European (WE), African-Caribbean (AC), and South Asian (SA) patients with type 2 diabetes mellitus (T2DM).Materials and methodsPatients with new diagnosis of T2DM, aged ≥ 18 years from January 2000 (n = 69,436) and their age-sex-ethnicity matched non-diabetic controls (n = 272,190) were identified from UK primary care database. Incidence rates rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…At diagnosis the rates of comorbidities were 30% in white Europeans compared with 11% of African-Caribbean and South Asian populations [86]. Clear distinctions in the incidence of chronic kidney disease have been found, which is higher in white Europeans than both African-Caribbean and South Asian populations [86]. Ethnic differences in the incidence of major cardiovascular diseases are also apparent; coronary heart disease is highest among South Asians, whereas African-Caribbean people experience significantly lower rates of coronary heart disease compared with white Europeans and South Asians, but rates of stroke do not differ by ethnicity [86,87].…”
Section: Glycaemic Control Diabetes Complications and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…At diagnosis the rates of comorbidities were 30% in white Europeans compared with 11% of African-Caribbean and South Asian populations [86]. Clear distinctions in the incidence of chronic kidney disease have been found, which is higher in white Europeans than both African-Caribbean and South Asian populations [86]. Ethnic differences in the incidence of major cardiovascular diseases are also apparent; coronary heart disease is highest among South Asians, whereas African-Caribbean people experience significantly lower rates of coronary heart disease compared with white Europeans and South Asians, but rates of stroke do not differ by ethnicity [86,87].…”
Section: Glycaemic Control Diabetes Complications and Mortalitymentioning
confidence: 99%
“…Clear distinctions in the incidence of chronic kidney disease have been found, which is higher in white Europeans than both African-Caribbean and South Asian populations [86]. Ethnic differences in the incidence of major cardiovascular diseases are also apparent; coronary heart disease is highest among South Asians, whereas African-Caribbean people experience significantly lower rates of coronary heart disease compared with white Europeans and South Asians, but rates of stroke do not differ by ethnicity [86,87]. Detailed investigations in the SABRE cohort are providing evidence for the mechanisms which may underlie these ethnic patterns in cardiovascular diseases.…”
Section: Glycaemic Control Diabetes Complications and Mortalitymentioning
confidence: 99%
“…Previous studies investigating this association have been impeded by the need to use complete record analysis due to missing data in ethnicity, which can create systematic bias in estimates. 33 The use of our approach would help overcome this limitation.…”
Section: Findings In Relation To Other Evidence and Implicationsmentioning
confidence: 99%
“…Sone et al found-in a relatively small cohort study-that a high WC value alone is not sufficient to raise the risk of CVD events significantly and is not an independent risk factor in Japanese diabetic patients [26]. Previous study found that the risk of developing long-term MACE differed in different populations [27]. Few studies have investigated sex differences in the relationship between WC and CVD in Western populations.…”
Section: Introductionmentioning
confidence: 99%